Stent Omission after Ureteroscopy and Lithotripsy (SOUL) in the Michigan Urological Surgery Improvement Collaborative (MUSIC): study protocol for a pragmatic prospective combined randomized and observational clinical trial - Russell E. N. Becker; Stephanie Daignault-Newton; Elaina Shoemaker; Dennis Sitek; Jennifer M. Thelus; Sabrina Clark; Adam Martin-Schwarze; Catherine Spino; Noelle E. Carlozzi; William J. Meurer; Anne E. Sales; Casey A. Dauw; et al. (Trials)
Abstract Background Ureteral stents are placed by urologists to ensure ureteral patency in the postoperative period following ureteroscopy to treat kidney stones, with the goal to reduce complications. However, ureteral stents themselves cause pain and urinary symptoms in many patients that can lead to morbidity. Professional society guidelines support stent omission after uncomplicated ureteroscopy, which represents most cases. Despite this, ureteral stents are utilized in more than 80% of all ureteroscopy procedures. One reason for guideline discordance is the low level of evidence supporting stent omission recommendations. Studies are inconclusive on whether stents increase pain and complications. A recent Cochrane review concluded higher quality and large trials are needed to inform decision-making. Furthermore, there is a lack of studies evaluating health-related quality of life (HRQOL), patient-reported outcomes (PROs), and unplanned healthcare utilization. Another factor is that prospective clinical trials are hindered by patient reluctance to be randomized to either stent placement or omission. The outcomes of patients who decline randomization have been ignored in trials, limiting the generalizability of the evidence. Methods Through collaboration with patient partners, we developed a pragmatic multi-center combined randomized and observational cohort study in a quality improvement collaborative. Patients will be prospectively enrolled into a randomized cohort in which assignment to ureteral stent omission (vs. placement) is determined in the operating room using a web-based randomization platform. Patients who decline randomization are invited to take part in an observational (real-world) cohort in which the determination of stent use is at the discretion of the urologist. Patients in both cohorts will complete preoperative and postoperative assessments of PROs including pain, urinary symptoms, interference with usual activities, time taken off work or school, and treatment satisfaction. Unplanned healthcare utilization within 30 days postoperatively will be assessed by review of the electronic health record. Severe adverse events will be recorded. A subgroup of patients and urologists will also participate in qualitative semi-structured interviews focusing on knowledge, preferences, and practice patterns regarding ureteral stenting. Interview transcripts will be thematically analyzed. Discussion This study is designed to evaluate the HRQOL and 30-day healthcare utilization of patients undergoing ureteral stent omission compared to stent placement following uncomplicated ureteroscopic treatment of upper urinary tract stones. Additionally, patient and urologist opinions and preferences related to ureteral stenting will be explored through qualitative interviews, with the aim of identifying key barriers and facilitators of practice change related to stenting practices. Trial registration ClinicalTrials.gov, NCT05866081. Registered on 19 May 2023.